Getting by estates, class and culture in austerity Britain - Mckenzie, Lisa 1968- (Policy Press, 2023)
Over the past thirty years, the United Kingdom's poor have become increasingly stigmatised, while many poor communities have become the subject of great public concern and media scorn. In this book, Lisa McKenzie offers rare insight into life in one of these neighbourhoods, St Ann's Estate in Nottingham. Notorious for containing many of the city's gangs, guns, and drugs, the area is also known as the place where the unemployed and the feckless take up as long-term residents. As a former inhabitant of St Ann's, McKenzie is able to delve into a community often wary of outsiders, providing an important account of the effects of recent policy changes and the complexities faced by those living in poor neighbourhoods in contemporary Britain